BROADBAND SYNTHETIC APERTURE BOREHOLE RADAR INTERFEROMETRY - Mason I.; Osman N.; Liu Q.; Simmat C.; Li M. (My University, 2001)
Trials in mines have established that wideband VHF borehole radars (BHR), working in the 10-100-MHz band, can be used to probe the rockmass between boreholes over ranges from <5 m to as much as 150 m with submeter resolution. There is evidence that ore bodies reflect these radar signals both specularly and diffusely, much as the ground/air interface does when overflown by synthetic aperture radar (SAR). In both SAR and BHR, multiple flight lines, together with diffuse reflections admit the possibility of developing interferometric 3D images of the object. This paper examines the possibility of imaging buried objects in three dimensions by interferometrically combining broadband VHF borehole radar profiles shot in adjacent pairs of boreholes. Broadbanding in BHR has the advantage of releasing the image from 2nπ phase ambiguities, but practically, interferometric borehole radar (InBHR) needs high signal-to-noise ratios (SNR) to avoid noise capture. This means that 3D InBHR is limited to ranges in wavelengths which are less than the rock's attenuation factor Q. Interferometric methods are developed which are capable of mapping ore bodies and other structures in three dimensions. Tangent plane migration methods are developed here in order to reconstruct surfaces that lie in the near-field of sparse interferometric arrays.
Keywords: BOREHOLE RADAR; INTERFEROMETRY; 3D IMAGING; SPARSE ARRAY; TANGENT PLANE MIGRATION